Patient outcomes and survival following surgery for spinal metastases. (4th March 2021) - Yaari, Lee Shaul; Novack, Lena; Shemesh, Shai; Sidon, Eli; Haviv, Barak; Sheinis, Dimitri; Ohana, Nissim
Abstract : Context : There is no consensus on the preferred treatment for patients with spinal metastases. Little is known about the outcomes of surgery for this population. The objectives of this paper are to examine the outcomes of surgery among patients with spinal metastases suffering from cord compression (CC) or intractable pain (IP). Design: Retrospective, descriptive (level 4) case series. Setting: Rabin Medical Center, Israel. Participants: 61 patients undergoing surgery for spinal metastasis in a tertiary care hospital. Patients were divided into two groups: those with spinal CC and those with IP only. Interventions: Surgery due to CC or IP among patients with spinal metastases. Outcome measures: Frankel scale to assess neurological status, ambulatory and incontinence status, which were examined before surgery, at discharge and at last follow-up. Endpoints were death or latest follow-up visit. Survival and postoperative complications were documented. Results: There was no significant difference in Frankel score before and after surgery among patients with CC (mean score 3.5 and 3.4 respectively, P = 0.62). Complete incontinence rates significantly increased in patients with CC between preoperative and last follow-up examinations (13.6% vs. 20%, respectively, P = 0.05). Median survival of CC and IP groups was 201 and 402 days, respectively (P = 0.32). Complication rate was 41.4%. Conclusion: In our cohort, Frankel score and walking capability of patients with CC did not change postoperatively, but continence status deteriorated over time. Surgeons should advise patients on expected surgical outcomes, especially in non-ambulatory and incontinent patients.